2009
DOI: 10.4070/kcj.2009.39.12.538
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-B-Type Natriuretic Peptide in Overweight and Obese Patients With and Without Diabetes: An Analysis Based on Body Mass Index and Left Ventricular Geometry

Abstract: Background and ObjectivesSeveral recent studies have shown that there is an inverse relationship between plasma B-type natriuretic peptide (BNP) and body mass index (BMI) in subjects with and without heart failure. Obesity frequently coexists with diabetes, so it is important to consider the relationship between diabetes and natriuretic peptide levels. We evaluated the influence of diabetes on the correlation of BNP and BMI.Subjects and MethodsWe examined 933 patients with chest pain and/or dyspnea undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…A huge number of bioactive substances are increased in plasma of patients with obesity, such as noradrenaline, angiotensin II, vasopressin, endothelins, and some cytokines, which typically increase (rather than reduce) the production/secretion of CNH by cardiomyocytes (Table 1 and Fig. 2) [11][12][13][15][16][17]. Also insulin was reported in one study to increase ANP secretion and gene expression in cultured rat cardiomyocytes, while glucose has no effect [87].…”
Section: Role Of Sex Steroid Hormonesmentioning
confidence: 97%
See 3 more Smart Citations
“…A huge number of bioactive substances are increased in plasma of patients with obesity, such as noradrenaline, angiotensin II, vasopressin, endothelins, and some cytokines, which typically increase (rather than reduce) the production/secretion of CNH by cardiomyocytes (Table 1 and Fig. 2) [11][12][13][15][16][17]. Also insulin was reported in one study to increase ANP secretion and gene expression in cultured rat cardiomyocytes, while glucose has no effect [87].…”
Section: Role Of Sex Steroid Hormonesmentioning
confidence: 97%
“…In women, estrogens may promote a gynoid distribution of body fat [58] and also increase the BNP production/secretion by cardiomyocytes [11,46,64,65]. On the other hand, the results of the Dallas Heart Study [62, 63] suggested that androgens may regulate the cardiac endocrine function.…”
Section: Role Of Sex Steroid Hormonesmentioning
confidence: 98%
See 2 more Smart Citations
“…To illustrate its magnitude, it is useful to compare the impact of theophylline use on NT-proBNP levels in regard to the effects of other covariates. Serum levels of NT-proBNP increase with age and are inversely associated with BMI [25,26] . If the analysis is restricted to our patients with asthma, COPD or respiratory muscle weakness, theophylline use has the same effect on the ln-transformed NTproBNP values as an 8-year decrease in age and a BMI increase of 11.…”
Section: Discussionmentioning
confidence: 99%